Multiple perspectives technology appropriation : analysis of open source software implementation failure - Alias, Rose Alinda (Penerbit UTM, 2010)
Adoption of new technology such as Open Source Software (OSS) is one of the important issues in organizations. Despite being considered as cost effective by many organizations, OSS implementation still encounters many challenges. This paper describes a case study conducted at one of Malaysia’s public universities which initially adopted Open Source based applications but then later rejected them. An integrated framework that combines a multiple perspectives approach and the Model of Technology Appropriation is proposed in this study. This framework facilitates the understanding of why and how organizations adopt and use OSS. The study identified various criteria influencing the OSS appropriation process from multiple perspectives in the organization as well as its status of OSS appropriation. This understanding assists in effective implementation decisions which could lead to more effective use of the OSS technology.